Tests of swap bodies monitoring system - A. A. Artyushin; N. E. Evtyushenkov; E. P. Shilova; A. A. Grishin (Сельскохозяйственные машины и технологии, 2015)
Swap bodies using at agricultural freights is very popular now. Thus the number of vehicles is reduced, operational costs are cut. Efficiency of swap bodies application increases at introduction of transport monitoring system for the purpose of the centralized remote supervision for its movement control. Swap bodies monitoring system was tested, its working ability influence on efficiency of transport service were studied. The block of data acquisition and transfer for swap bodies monitoring system was worked out and tested. Due to indicator of a body filling operability the sensor of level of bulks was checked. The speed of indicator operation when body filling makes 5-10 seconds. Thus filling of a swap body is displayed on the monitor in control office. Location of a swap body display on the monitor in control office was defined by means of imposing of the pictogram on a district map with the indication of coordinates. The device for determination of duration of autonomous work of system works within 2 days, time of a battery charging made 3 h. The device for the swap bodies monitoring system carries out functions in full, providing remote supervision over work of system.